New additions to the shallow-water hydroids (Cnidaria: Hydrozoa) of the French Lesser Antilles: Martinique - Galea, Horia R. (Zootaxa, 2013)
The present report provides the first general account of the shallow-water hydroids (excluding Eudendriidae) of Martinique, French Lesser Antilles. Of a total of 92 species recorded, 10 athecates and 31 thecates are discussed here, with the remaining species having been the subject of earlier accounts. Six hydroids, namely Halecium discoidum, H. xanthellatum, Sertularella calderi, Antennella peculiaris, A. similis, and A. tubitheca, are new. Previously unreported data on the nematocyst complement of Heterocoryne caribbensis Wedler & Larson, 1986, Ectopleura mayeri Petersen, 1990, Ralpharia gorgoniae Petersen, 1990, and seven hebellid species are provided. The gonotheca and the gonophore of Hebellopsis communis Calder, 1991 are described for the first time, allowing a genus transfer to Anthohebella Boero et al., 1997. Thyroscyphus longicaulis Splettstösser, 1929, a species whose gonosome remained unknown until now, is redescribed based on new, fertile material of both sexes. The occurrence of Antennella quadriaurita Ritchie, 1909 in the Caribbean is questioned upon comparison of its cnidome with that of specimens from Tristan da Cunha, the type locality of this species. An unexpectedly wide morphological variation is noted for Aglaophenia rhynchocarpa Allman, 1877. Specimens corresponding to the Caribbean Gymnangium longicaudum (Nutting, 1900), are shown to be indistinguishable morphologically from a taxon described earlier from Brazil, Gymnangium allmani (Marktanner-Turneretscher, 1890), the latter having priority. Thorough descriptions are provided for the new, lesser known or unidentifiable species, while the common taxa are accompanied by brief remarks and/or distributional data. Illustrations are provided for each species discussed in order to justify their identification, and to facilitate identification by others. A checklist at the end of this work incorporates records of 101 species of hydroids reported from Martinique, both occurring in the present collection and cited in the literature.